Preparation, characterization, and thermal stability of B2O3-ZrO2 - Theresia Debora Simbolon; Risfidian Mohadi (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2017)
Synthesis of the borate-based compound with ZrOCl2 to form B2O3-ZrO2 has been conducted. The compound was characterized by FT-IR spectrophotometer, X-ray diffraction, acidity and thermal stability test. The results showed that the FT-IR main vibration spectrum of B2O3-ZrO2 compound has appeared at wave number 401.2 cm-1 for Zr-O bonding vibration, 617.2 cm-1 for B-O-B bonding vibration and 910.4 cm-1 for B-O bonding vibration. The XRD diffraction pattern shows B2O3-ZrO2 compound has an amorphous structure. The FT-IR spectrum after saturated with ammonia and potentiometric titration indicates that the compound of B2O3-ZrO2 has acidic properties with a strong level of acidity. Thermal stability test shows that the B2O3-ZrO2 compounds have high stability on temperature with increasing crystallinity after the compound was heated at 700 °C. Keywords: B2O3-ZrO2, impregnation, thermal stability.